QUR'ANIC CHARACTER EDUCATION IN MUTAROBBI AT MTsS MAGHFIRAH ISLAMIC LEADERSHIP BOARDING SCHOOL (MILBoS) - Vita Lastriana Candrawati; Zikry Septoyadi (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2025)
The background of writing this was the formation of Qur'anic character in mutarabbi at MTsS Maghfirah Islamic Leadership Boarding School (MILBoS), the main reason why the researcher chose this title, because the morals or character of Rasulullah Shallallahu 'Alaihi Wasallam is the Qur'an, as which was explained by Sayyidah 'Aisyah Radhiallahu 'Anha when she was asked by a friend about the morals of Rasulullah Shallallahu 'Alaihi Wasallam and at MTsS MILBoS all activities or activities must be based on strong and clear arguments from the Al-Qur'an and As-Sunnah which will make or shape the character of the mutarabbi or MILBoS students into Qur'ani characters, the vision and mission of MTsS MILBoS is also based on the Qur'an and also includes the Qur'ani character found in Rasulullah Shallallahu 'Alaihi Wasallam, namely being qurrata 'ayun (a comforter for everyone, especially their parents in this world and the hereafter) and lilmuttaqiin imama (imam or leader for those who are pious). This type of research is field research, because this research raises data that actually exists in MILBoS in the formation of Qur'anic character. With research subjects, the MTsS MILBoS principal and teachers or murabbi, This research is also included in qualitative research with descriptive methods. Data collection techniques in this research used interviews, observation and documentation. The results of this research show that Qur'anic character education for mutarabbi or students at MTsS MILBoS runs and is managed neatly and regularly. It is hoped that the results of this research can be used as relevant reference material for future researchers, especially in the world of educational management